(untitled) - FAO (Rome, Italy, 1999)
The book adresses the chalenges and opportunities of fisheries monitoring that are common to many fisheries. It discusses around five main themes: Rationale for monitoring programmes - conceptual and legal frameworks; Perspectives on monitoring from key stakeholders; Designing, executing and analysing monitoring programmes; Key components and issues for monitoring programmes; and Integrated monitoring.
Keywords: fisheries - economic aspects